Composição química, atividade antimicrobiana, inseticida e antioxidante do óleo essencial e extratos de Guarea kunthiana A. Juss - Pandini, Jessica Angela (2014)
The present study aimed to determine the chemical composition of the essential oil of Guarea kunthiana A Juss by the method of gas chromatography coupled to mass spectrometry (GC-MS), evaluate the antimicrobial activity of this oil against different Gram positive and Gram negative bacteria, and yeast: Escherichia coli, Salmonella entérica subsp. entérica, Pseudomonas aeruginosa, Proteus mirabilis, Klebsiella pneumoniae, Staphylococcus aureus, Enterococcus faecalis, Staphylococcus epidermidis, Bacillus subtillis e Candida albicans. Evaluate the antimicrobial activity of essential oil and aqueous extracts, ethyl acetate and alcohol against different serotypes of Salmonella in poultry origin: Enteritidis, Infantis, Typhimurium, Heildelberg, Mbandaka, Give, Saintpaul, Orion, Gallinarum e Agona. Determine the insecticidal activity of the oil and extracts against larvae and adults of Alphitobius diaperinus (Panzer 1797) (Coleoptera: Tenebrionidae), and finally evaluate the antioxidant activity of essential oil and extracts by the capture of the hydrazyl free radical 2,2-diphenyl-1-picryl (DPPH). The analyses of GC-MS resulted in the identification of 13 constituents, representing 96.52% of the total area on the essential oil. The main compounds identified were α-Zingiberene (34.48%), β-Sesquifelandreno (22.90%) and α-Curcumene (16.17%). Regarding antimicrobial activity of the essential oil was effective against all micro-organisms tested except for the bacteria E.coli e K. pneumoniae, which presented themselves resistant to the action of the oil. For Salmonella serotypes evaluated, the essential oil had greater activity against serotypes Infantis, Typhimurium e Give, with values of MIC and MBC of 54,6 μg/mL for both, for the other serotypes tested the action of the oil was classified as moderate, weak and inactive. Regarding extracts all serotypes tested were susceptible to the extract of ethyl acetate, followed by alcoholic extract, the aqueous extract showed no antimicrobial activity. The results concerning the insecticidal activity of the essential oil revealed that it provided better activity against larvae at a concentration of 200 mg / mL (28%) compared to adults the mortality rate was low (12%) at this concentration. With the extracts, the best results were found for the alcoholic extract at a concentration of 10%, with values of 34 and 44% respectively, adults and larvae. The values of antioxidant activity showed no significant differences between the synthetic antioxidant butylated hydroxytoluene (BHT), essential oil and alcoholic extract, revealing that both the essential oil as alcoholic extract of G. kunthiana demonstrated high antioxidant capacity